Expansion of activated cxcr5+icos+ tfh cells and plasmablasts induced by seasonal influenza vaccine is impaired in anti-il-6r treated rheumatoid arthritis patients - Romao, V.C. (2019)
Objectives: To investigate the importance of IL-6 for the in vivo differentiation of human Tfh cells, taking advantage of influenza vaccination in patients under anti-IL-6R therapy.